ENTEROSORPTION AND ITS CLINICAL EFFECTIVENESS IN COMPLEX TREATMENT OF ACUTE INTESTINAL INFECTIONS IN CHILDREN - A. A. Novokshonov; N. V. Sokolova ("Paediatrician" Publishers LLC, 2011)
The article analyzes methods of enterosorption and its role and place in clinical practice; classification and mechanism of action of enterosorbates, pathogenetical and clinical aspects of enterosorption in treatment of acute intestinal infections (AII) and other gastroenterological pathology. Authors give brief characteristics, indications and dosing regimen of enterosorbents. The results of clinical efficacy studies of Russian enterosorbates based on hydrolyzed lignin - «Filtrum-STI» and «Filtrum-Safari» in complex treatment of AII in children are described.